Charlie bone and the hidden king eaudiobook - Nimmo, Jenny (Children of the Red King, 2006)
The next installment in the New York Times bestselling series, CHARLIE BONE AND THE HIDDEN KING In Charlie’s most perilous adventure yet, the shadow from the Red King’s portrait has escaped. Strange things start to happen at Bloor’s Academy. But, with the help of a mysterious force, Charlie and his friends are closer to discovering the truth about Charlie Bone’s father. Children of the Red King Series Book 1: Midnight for Charlie Bone Book 2: Charlie Bone and the Time Twister Book 3: Charlie Bone and the Invisible Boy Book 4: Charlie Bone and the Castle of Mirrors